Análise numérica da estabilidade de sólitons ópticos espaço temporais (2+1) em um guia planar com não linearidade cúbico-quíntica e efeito da relaxação temporal em acoplador direcional duplo assimétrico para obtenção de funções lógicas - Fraga, Wilton Bezerra de (2010)
In this work, we have presented a numerical analysis of the stability of optical bullets (2+1), or spatiotemporal solitons (2+1), in a planar waveguide with cubic-quintic nonlinearity. The optical spatiotemporal solitons are the result of the balance between the nonlinear parameters, of dispersion (dispersion length, LD) and diffraction (diffraction length, Ld ) with temporal and spatial auto-focusing behavior respectively. With the objective of ensure the stability and preventing the collapse or the spreading of pulses, in this study we explore the cubic-quintic nonlinearity with the optical fields coupled by XPM and considering several values for the non linear parameter α. We have shown the existence of stable light bullets in planar waveguide with cubic–quintic nonlinearity through the study of spatiotemporal collisions of the light bullets. Also we have presented a numerical analysis of the dual-core fiber coupler operating with instantaneous and relaxation approximation of the Kerr model for generation of the all- optical logic gates and half-adder circuit. To implement this optical circuit we used the fiber coupler in a structure asymmetric where we are interested in the transmission characteristics, the Extinction Ratio as a function of the time relaxed (τR ) and of the phase difference (ΔΦ) between the pulses inputs, the length normalized (LN), the figure-of-merit of the logic gates (FOMELG (dB) and thus ensure the operation of the dual-core fiber coupler for generation of the all- optical logic gates and the half-adder operating in relaxed and instantaneous nonlinear Kerr model.